Analisis kesalahan dalam menyelesaikan soal persamaan kuadrat siswa SMK Kesehatan - Rahmi Hidayati (STKIP PGRI Banjarmasin, 2019)
The purpose of this study was to find out the location of errors in solving quadratic equations and learning completeness in the material of quadratic equations. The data sources of this study are 65th grade Vocational School students in Pharmacy majoring in. The method used in this research is descriptive method. The data collection technique used is the test and analysis used by percentage techniques. The results of this study are the location of errors experienced by students in resolving quadratic equations using the abc formula more dominant by using step 1, namely determining the values of a, b, and c, especially in quadratic equations which are not standardized and student learning completeness has not been achieved